Pengaruh Lingkungan Kerja dan Manajemen Konflik Terhadap Kinerja Karyawan PT KB Finansia Multi Finance Kreditplus Cabang Tambun: The Impact of the Work Environment and Conflict Management on Employee Performance at PT KB Finansia Multi Finance Kreditplus, Tambun Branch - Dany Rahman; Mahmud Syarif (CV Warnak Johanna Nusantara, 2025)
Performance is the result of work achieved by a person in their efforts to achieve organizational or corporate goals. The performance of employees in a company does not always increase and sometimes even decreases, this is due to various conflicts and stress in the workplace environment that must be faced by employees. The purpose of this study was to determine the effect of work environment and conflict management on the performance of employees of PT KB Financial Multi Finance Kreditplus Tambun Branch, where work environment variables affect employee performance, however, conflict management variables do not affect employee performance. The population is all employees of PT KB Finansia Multi Finance Kreditplus Tambun Branch, totaling 44 people. The data obtained from the questionnaire was tested with validity and reliability tests and hypothesis testing using multiple linear regression, determination test (R2), F test, and T-test. The results showed that employee performance was significantly influenced partially by work environment factors. With a Thitung value of 6.731> from Table 2.019. The compensation management variable has no significant effect partially on employee performance sig 0.996> from 0.05. With a Thitung value of 0.005 < from Ttabel 2.019. From the results of the f-test calculation, it can be seen that the work environment variables and conflict management together affect employee performance.